SIRT3 Regulation Under Cellular Stress: Making Sense of the Ups and Downs - Marcus, Joshua M.; Andrabi, Shaida A. (Frontiers in Neuroscience, 2018)
Sirtuin 3 (SIRT3) is an NAD+ dependent deacetylase that resides primarily in mitochondria and functions to maintain mitochondrial homeostasis under stress. SIRT3 expression has been observed to change under a number of different stresses in multiple tissues and model systems. Inconsistencies in the literature with regards to how and when SIRT3 protein levels change indicates that the mechanism of SIRT3 regulation is multi-faceted. Alterations in SIRT3 have been observed in experimental models cellular stress, however the effect these changes have on mitochondrial health remain unknown. Neurons are highly dependent on proper mitochondrial function for their survival. SIRT3 dynamics and function have been studied using models of genotoxic, metabolic, and oxidative stresses, although it remains unclear how SIRT3 is being regulated under these conditions. A closer look into SIRT3 regulation under stress conditions in various model systems will help incorporate the many SIRT3 regulatory mechanisms at play in disease states. In this review, we describe the observations that have been made about SIRT3 protein modulation under basic stress conditions. We then point out consistencies and contradictions in these observations and what they mean. Lastly, we present the observations made in the complicated neuronal stress of stroke. We hope that this review will help consolidate the ambiguous SIRT3 literature and provide a framework for investigation of SIRT3 regulation during stress response.